Using Smart Control System to Enhancement the Split Air Conditioning System Performance - Mohammed, Farag Mahel; Mohammed, Jamal Abdul-Kareem; Jabbar, Mustafa Abdul-Sattar (Al-Khwarizmi Engineering Journal, 2017)
In IRAQ, the air conditioners are the principal cause of high electrical demand. In summer, the outer temperature sometimes exceeds 500C which significantly effects on the A/C system performance and power consumed. In the present work, the improvement in mechanical and electrical performance of split A/C system is investigated experimentally and analytically. In this paper, performance and energy saving enhancement of a split-A/C system was experimentally investigated to be efficiently compatible with elevated temperature weathers. This improvement is accomplished via Smart Control System integrate with Proportional-Integral- Differential PID algorithm. The PIC16F877A micro-controller has been programmed with the PID and PWM codes to control the speed of the proposed DC condenser fan over wide range of speed, also it has been programmed to have a smart characteristics to protect the A/C system parts as the ability to detect a refrigerant leakage, condenser fan stop, and any obstacles for the fan air flow. A comparative study between the conventional and enhanced A/C system is performed. The results show that the proposed system exhibits better performance and saves more energy than the conventional one. The Coefficient of Performance (COP) of the split- A/C system are improved by about 20.56%.